2017
DOI: 10.4067/s0718-221x2017005000023
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activities of some bark and wood extracts against wood-damaging insects

Abstract: This study investigates the larvicidal activities of plant extracts and tannins against wood-damaging insects. Scots pine (Pinus sylvestris), beech (Fagus orientalis), and poplar wood (Populus tremula) were subjected to larvae of Spondylis buprestoides (Coleoptera: Cerambycidae) by impregnating them with mimosa (Acacia mollissima), quebracho (Schinopsis lorentzii) and redpine bark (Pinus brutia) extracts. At the end of the 6-month experiment, the numbers of dead and live larvae as well as the mean mass losses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A literature survey regarding the biological activities of the phytochemical constituents of our studied extracts in GC–MS profiling Table 2 showed that there are many studies reporting many biological activities of the same obtained constituent in our study from a variety of botanical extracts. Many biological activities including the insecticidal activity are recorded for the following constituents: 9-2-Methyl-Z, Z-3, 13 octadecadienol (terpenoid) which act as a Pesticide, herbicide, insecticide and as a pheromone [ Adeyemi et al, 2017 ], the second constituent: 9,17-Octadecadienal, (Z)- an insecticidal Aldehydecompound and act also as an Antieczemic, Nematicide, Antihistaminic and Antimicrobial [ Oni et al, 2020 ], the third constituent, Nonanoic acid, 9-oxo-, methyl ester a Potent antifungal, Antioxidant, Potent Antimicrobial [ Sen et al, 2017 ] beside its larvicidal activity [ Sen et al, 2017 ], fourthly 9,12-Octadecadienoic acid (Z,Z)- known as linoleic acid a Polyunsaturated Fatty acid which has many activities like Insecticidal activity [ Christiana et al, 2019 ], Anti-inflammatory, Hypocholesterolemic Cancer preventive, Hepatoprotective, Nematicide Insectifuge, Antihistaminic Antieczemic, Antiacne, 5-Alpha reductase inhibitor Antiandrogenic, Antiarthritic and Anticoronary, [ Adeyemi et al, 2017 ] and finally Octasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecamethyl- which has an antimicrobial activity)[ Ahmed et al, 2020 ] beside its insecticidal activity [ Abdullah, 2019 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey regarding the biological activities of the phytochemical constituents of our studied extracts in GC–MS profiling Table 2 showed that there are many studies reporting many biological activities of the same obtained constituent in our study from a variety of botanical extracts. Many biological activities including the insecticidal activity are recorded for the following constituents: 9-2-Methyl-Z, Z-3, 13 octadecadienol (terpenoid) which act as a Pesticide, herbicide, insecticide and as a pheromone [ Adeyemi et al, 2017 ], the second constituent: 9,17-Octadecadienal, (Z)- an insecticidal Aldehydecompound and act also as an Antieczemic, Nematicide, Antihistaminic and Antimicrobial [ Oni et al, 2020 ], the third constituent, Nonanoic acid, 9-oxo-, methyl ester a Potent antifungal, Antioxidant, Potent Antimicrobial [ Sen et al, 2017 ] beside its larvicidal activity [ Sen et al, 2017 ], fourthly 9,12-Octadecadienoic acid (Z,Z)- known as linoleic acid a Polyunsaturated Fatty acid which has many activities like Insecticidal activity [ Christiana et al, 2019 ], Anti-inflammatory, Hypocholesterolemic Cancer preventive, Hepatoprotective, Nematicide Insectifuge, Antihistaminic Antieczemic, Antiacne, 5-Alpha reductase inhibitor Antiandrogenic, Antiarthritic and Anticoronary, [ Adeyemi et al, 2017 ] and finally Octasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecamethyl- which has an antimicrobial activity)[ Ahmed et al, 2020 ] beside its insecticidal activity [ Abdullah, 2019 ].…”
Section: Discussionmentioning
confidence: 99%
“…For black seed extracts ( N. sativa Linn), 5 compounds were found in petroleum ether extract, 6 compounds in methylene chloride extract, and 8 compounds in methanolic extract. Although G C -MS Profiling of petroleum ether extract of black seed ( N. sativa Linn) gave the least number of constituents (5 compounds), it showed the highest LC50 of 40.7748 ppm and LC 90 of 681.5116 ppm among all extracts which may be explained to the nature of the extract and its constituents, especially four of the five constituents showed insecticidal and larvicidal activity which are 9,12-Octadecadienoic acid (Z,Z)- [ Christiana et al, 2019 ], Cis-11,14 –Eicosadieonic acid -methyl ester[ Akpuaka et al, 2013a , Akpuaka et al, 2013b ], Nonanoic acid, 9-oxo-, methyl ester[ Sen et al, 2017 ] and 9- Oxononanoic acid[ Gunstone et al, 2007 , Amin et al, 2018 ] while the fifth major constituents 1-Eicosene ((Alkene)(50.331%) ( Table 2 ) which is also a major constituent of A. altissima flower oil [ Rezae et al, 2006 ], however, there is a similar compound called 9-Eicosene in N. sativa [ Choo et al, 2001 ] and another similar compound called 3-Eicosene in the previous studies which exhibit Insecticidal activity [ Anthony et al, 2013 ], Antimicrobial, Antihyperglycemic [ Barathikannan et al, 2016 ], Cytotoxic Activity [ Barathikannan et al, 2016 ], [ Caboni et al, 2012 ]. The components present in black seed could now be obtained by total synthesis and the study of their insecticidal properties should make very interesting research studies for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Plant wood can be degraded by fungi and termites due to its biological origin (Syofuna et al 2012). One of the most important causes of wood damage in plants are insects (Sen et al 2017) that produce technical and economic losses (Ssemaganda et al 2011). Sen et al (2017) reported that the most important borer insects are those belonging to the Cerambycidae, Anobidae and Lyctidae families.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important causes of wood damage in plants are insects (Sen et al 2017) that produce technical and economic losses (Ssemaganda et al 2011). Sen et al (2017) reported that the most important borer insects are those belonging to the Cerambycidae, Anobidae and Lyctidae families. A wood-damaging insect type is Xylotrechus arvicola, which belongs to the Cerambycidae family from the Coleoptera class.…”
Section: Introductionmentioning
confidence: 99%
“…But, this type of non-biodegradable chemicals has been limited in many countries, in last years due to their undesirable effects on environment and human health (Pánek et al 2014). Therefore, latest researches have been focused on finding non-toxic eco-friendly substances obtained from natural and medicinal materials such as plant or fungi (Sen et al 2009, Nurudeen et al 2012, Sen et al 2017, Bahmani and Schmidt 2018.…”
Section: Introductionmentioning
confidence: 99%